2016
DOI: 10.1093/rheumatology/kew366
|View full text |Cite
|
Sign up to set email alerts
|

Chronic signs of memory B cell activation in patients with Behçet’s disease are partially restored by anti-tumour necrosis factor treatment

Abstract: We show significant deviations in the memory B cell compartment, related to disease activity and therapeutic efficacy. Pronounced molecular impairments were seen in the fast-responding IgM-memory and the mucosal IgA-memory B cells. Because of the demonstrated abundance of B cells in affected tissue, we hypothesize relocation of memory B cells to the site of inflammation could account for the deviations found in blood of BD patients. These peripheral B cells are easily accessible as a marker to monitor therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The disparities found between studies could be related to the use of different anti-TNF agents, disease activity, cohort size and previous treatments administrated to RA patients. Previous works have demonstrated that TNF-inhibitors affect memory B cell subpopulations not only in RA, but also in other inflammatory diseases [ 16 , 19 , 31 , 36 39 ]. In fact, circulating naive B cells and class-switched memory B cells were found to be normally present in peripheral blood of patients with Crohn’s disease, whereas IgM+ memory B cell numbers were reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disparities found between studies could be related to the use of different anti-TNF agents, disease activity, cohort size and previous treatments administrated to RA patients. Previous works have demonstrated that TNF-inhibitors affect memory B cell subpopulations not only in RA, but also in other inflammatory diseases [ 16 , 19 , 31 , 36 39 ]. In fact, circulating naive B cells and class-switched memory B cells were found to be normally present in peripheral blood of patients with Crohn’s disease, whereas IgM+ memory B cell numbers were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been shown that in patients with sarcoidosis, the increased blood levels of CD27-IgA+ memory B cells are normalized after treatment with infliximab [ 37 ]. Furthermore, it has been recently demonstrated that patients with Behçet's disease have significantly lower memory B cell numbers in peripheral blood, particularly CD27+IgA+ B cells, when compared to controls, but treatment with adalimumab restored to normal levels blood B cell numbers [ 39 ]. Of note, it has been previously shown that established RA patients have significantly lower levels of peripheral blood pre-switch IgD+CD27+ memory B cells when compared to healthy individuals, but treatment with infliximab restored the frequency of this B cell subpopulation to normal levels [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact causes of Behçet's disease (BD) are still unknown, and current knowledge suggested that BD could follow an autoimmune process induced by an infectious or environmental agent in genetically predisposed individuals. The major pathogenetic mechanisms underlying BD were linked to hyperactivity of neutrophils, gammadelta T (γδ T) lymphocytes, Th1 and Th17 lymphocytes, and down-regulation of regulatory T lymphocytes (Tregs) in the innate immunity system, and these have caused critical overproduction of proinflammatory cytokines, such as TNF-α, IL-1, IL-6, and IL-17 (10). However, growing evidence has suggested that B cells might also play a more eminent role in BD, which was not only responsible for antibody production but also involved in antigen presentation, pro-inflammatory cytokine secretion, and modulation of T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…The broad spectrum of symptoms that are alleviated by treatment with anti-TNF-α agents confirms the major role of TNF-α in the diverse manifestations of BD. Blocking of TNF-α downregulates pro-inflammatory T-cell subsets and restores the memory B-cell compartment [66][67][68]. Next to the immunologic effects of anti-TNF-α treatment, the beneficial effect on vascular BD disease suggests an effect on the vascular endothelial cells, but this is not yet evidenced in BD.…”
Section: Discussionmentioning
confidence: 99%